Exploring the value of the capability approach for vocational education and training evaluation: reflections from South Africa - Powell, Lesley; McGrath, Simon (Institut de Hautes Etudes Internationales et du Developpement (Graduate Institute of International and Development Studies), 2014)
In the late 1990s, South Africa was faced with the triple challenge of reforming the Apartheid divided institutional landscape of vocational education and training (VET) institutions; addressing equitable access to skills; and reorienting its skills development system to the nation’s insertion into the global economy. A wave of institutional reforms was enacted and a large programme of evaluative research followed in its wake. Whilst this body of work was both valuable and necessary, as significant practitioners in this programme we can see several of its limitations. Thus, we counterpose an alternative approach to evaluation that draws on the insights of the capabilities approach. By putting the needs of people first – rather than the needs of the economy – the capability approach brings to the forefront of VET evaluation the importance of social justice, human rights, and poverty alleviation. Such an approach pays better attention to what individuals and institutions value and are seeking to do, whilst retaining the economic rationale as an important part of such analysis; and insisting on the continued salience of evaluation for the improvement of delivery and outcomes.